Justice for Cut Intan Nabila: Integration of Islamic Law and Psychology in Adjudicating Cases of Violence Against Women - Hasan, Faradila; Rajak, Fioreza Ayulis Putri (The Center for Gender and Children Studies, the Institute for Research and Communing Service, State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2024)
This research examines the integration of Islamic law and psychology within the Indonesian criminal justice system to enhance protection for women victims of violence. Utilizing the domestic violence case of social media influencer Cut Intan Nabila as a case study, this research develops the Islamic-Psychological Judicial Framework (IPJF), which combines principles of Islamic law, understanding of trauma psychology, and best practices in the judicial system. Through juridical-normative analysis and an interdisciplinary approach, this study identifies gaps in the existing system and formulates strategies for IPJF implementation. The findings indicate that IPJF has the potential to increase the effectiveness of case handling, reduce revictimization, and enhance victim recovery. The implementation of IPJF is projected to transform legal culture to become more gender-responsive and victim protection-oriented, as well as serve as a potential model for other Muslim-majority countries.